A female with severe knee osteoarthritis and tibial pseudoarthrosis after stress fracture treated with knee endoprosthesis and tibial plating. Case report - Gabor Stępień; Marcin Żyliński; Tomasz Trzeciak (Chirurgia Narządów Ruchu i Ortopedia Polska)
Stress fracture of the lower extremity is a significant cause of decreased mobility in orthopedic patients. With repetitive stress on the bone tissue of the lower extremities, stress fractures occur in 50% of the cases, primarily involving the tibia. This article presents a method of managing the pseudoarthrosis of the tibia resulting from a stress fracture of the shinbone of a patient with advanced degenerative changes in both knee joints. This article presents the case of a 69-year-old woman with advanced degenerative changes in both knee joints and a significant varus deformity of both lower limbs. She developed a stress fracture in the proximal part of the left tibia, resulting in the formation of pseudoarthrosis. The authors describe a simultaneous left knee joint total knee replacement (TKR) procedure with limb axis correction using a long tibial stem (tibial extension) passing through the pseudoarthrosis and rotational stabilization of the tibia with an osteo-plate.